AN EMPIRICAL VERIFICATION OF THE COMMUNITY OF INQUIRY FRAMEWORK - Arbaugh, Ben (Online Learning, 2007)
The purpose of this paper is to report on the results of a study that examines whether the CoI dimensions of social, teaching and cognitive presence distinctively exist in e-learning environments. The rest of the paper is organized as follows. First, I will briefly review recent studies on the dimensions of this framework: social, cognitive, and teaching presence. Second, I discuss the development of the sample of MBA students in online courses over a two-year period at a Midwestern U.S. university and the items used to measure the CoI dimensions. Next, I will describe the results of an exploratory factor analysis, including an interpretation of the emerging factors. Finally, I will discuss how these findings relate to conclusions presented in Garrison’s review of recent research related to the CoI and present some possible directions for future research.